EVALUATION OF VILLAGE FUND BUDGET MANAGEMENT IN BUSINESS CAPITAL PARTICIPATION IN VILLAGE-OWNED ENTERPRISES - Jopang; La Taya; Sanawia (Halu Oleo University, 2024)
The provision of Village Fund Allocation is a manifestation of the fulfilment of the village's right to exercise its autonomy it grows and develops following the growth of the village itself based on diversity, participation, original autonomy, democratization, community empowerment, and increasing the role of Village Government in providing services and improving community welfare as well as spurring the acceleration of regional development and growth. This study aims to determine the evaluation and strategy in village fund management with capital participation from Village Funds. This research uses qualitative approaches and methodologies in data collection as well as data presentation. The informants in the study were all Village Governments in the Konawe Regency area that had village-owned enterprises with the criteria of Independent and Developing Villages, Problem Villages, and Developed Villages. The data analysis process in this study went through three stages: The First is data classification. Second, data interpretation is an activity that combines the results of the analysis with statements to find the meaning of data collected in the field to answer problems and researchers' efforts to interpret data that can be taken by reviewing symptoms based on their point of view, comparison with research that has been done. Third, data presentation. The strategy of mentoring and coaching by the local government, especially through the Village Community Empowerment Office of South Konawe Regency to encourage the development of Village-Owned Enterprises in each village, has not been able to answer the challenges and problems in business development.